Isolation film, battery cell, battery, and power using device
Patent Information
- Application Number
- CN202380060936.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-17
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-04-17
AI Technical Summary
然而,目前电池单体的循环性能较差,仍需要进一步提高
Smart Images

Figure CN119744476B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, specifically to a separator, a battery cell, a battery, and an electrical device. Background Technology
[0002] Battery cells have characteristics such as high capacity and long lifespan, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric cars, electric airplanes, electric ships, electric toy cars, electric toy ships, electric toy airplanes, and power tools, etc.
[0003] As batteries are used in a wider range of applications, the requirements for the performance of individual battery cells are becoming increasingly stringent. However, the current cycle performance of individual battery cells is relatively poor and still needs further improvement. Summary of the Invention
[0004] The embodiments of this application were made in view of the above-mentioned problems, and the purpose of this application is to provide a separator, a battery cell, a battery, and an electrical device.
[0005] The first aspect of this application provides a separating membrane, the separating membrane comprising a separating body and a polymer layer disposed on at least one surface of the separating body, the polymer layer comprising a liquid-retaining polymer, wherein the liquid-retaining polymer is added to a first solvent at 70°C to form a polymer system; the polymer system is allowed to stand at 70°C for 8 hours, and then allowed to stand at 25°C for ≥24 hours, and the polymer system is filtered through a 200-mesh filter to leave a first substance, wherein the mass of the liquid-retaining polymer is q in g; the mass of the first substance is m in g; the liquid-retaining polymer and the first substance satisfy: 5 ≤ m / q ≤ 1000; the adhesive force of the separating membrane is greater than or equal to 10 N / m.
[0006] Therefore, the separator in this embodiment includes a polymer layer, which includes a liquid-retaining polymer. The separator exhibits excellent adhesion properties, ensuring a tight bond between the separator and the electrode. This alleviates liquid shortage caused by increased gaps between electrodes during battery cycling, thereby improving the cycle performance of the battery cell. Furthermore, the liquid-retaining polymer is disposed on the surface of the separator. When in contact with the electrolyte, the polymer molecular chains expand and open, allowing the electrolyte to diffuse between the chains. The polymer molecular chains swell and adsorb, forming a three-dimensional interconnection network between the separator and the electrode. This network adheres to the electrode surface, bonding the separator and electrode together, further enhancing the stability of the electrode and separator structure and improving the cycle performance of the battery cell. Moreover, this three-dimensional interconnection network locks the electrolyte within itself, maintaining it within the electrode and separator structure. This improves the ion transport interface, facilitating the transport of active ions such as lithium and sodium ions, and further enhancing the cycle performance of the battery cell.
[0007] In some embodiments, the adhesive strength of the separator is between 10 N / m and 30 N / m. When the adhesive strength of the separator is within the above range, the separator has good adhesion performance, which is beneficial to improving the connection stability between the separator and the electrode. During the charge-discharge cycle of the battery cell, it reduces the risk of the distance between the separator and the electrode increasing, thereby allowing the electrode assembly to adsorb a larger amount of electrolyte, which is beneficial to improving cycle performance.
[0008] In some embodiments, the polymer layer includes an adhesive polymer, which includes one or more of epoxy resins, polyurethanes, silicones, polyimides, polyacrylates, polymethacrylates, and ethyl acetate (VAE emulsions). These adhesive polymers possess excellent adhesive properties.
[0009] Further optionally, the polyacrylates include ethyl polyacrylate.
[0010] In some embodiments, the ratio of the mass percentage of the liquid-retaining polymer to the mass percentage of the adhesive polymer, based on the total mass of the polymer layer, is (1 to 9):1. When the mass percentage ratio of the liquid-retaining polymer to the adhesive polymer is within the above range, both the adhesion and gelation properties of the polymer layer can be improved.
[0011] In some embodiments, the liquid-retaining polymer comprises a fluorinated polymer; the crystallinity of the fluorinated polymer, as determined by differential scanning calorimetry, is Xc1, where 0 < Xc1 ≤ 30%; the melting temperature of the fluorinated polymer is T. m1 Its unit is ℃, 0 < T m1 ≤140.
[0012] In some embodiments, the glass transition temperature of the fluorinated polymer is T. g1 Its unit is ℃, -150≤T g1 ≤60.
[0013] In some embodiments, the fluoropolymer includes at least one of the structural units represented by formula (A1) to formula (AIII).
[0014]
[0015] In equations (AI) and (AII), R 11 R 12 R 13 and R 14 Each independently comprises a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 R 12 R 13 and R 14 At least one of them contains a fluorine atom;
[0016]
[0017] In formula (AIII),
[0018] R 15 Includes single-bonded, substituted or unsubstituted C1-C3 alkyl groups; p is a positive integer selected from 1 to 3; n is a positive integer selected from 1000 to 30000.
[0019] In some embodiments, the liquid-retaining polymer further includes an ether polymer, wherein the ether polymer is formed into a sheet-like structure; the sheet-like structure is in (T m2 The elastic modulus G' - energy dissipation modulus G” curve was obtained by dynamic frequency scanning test at +20℃. The slope of the elastic modulus G' - energy dissipation modulus G” curve is K1, 1<K1<∞, T m2 ℃ represents the melting temperature of the ether polymer; optionally, 1 < K1 ≤ 100; further optionally, 1 < K1 ≤ 10.
[0020] In some embodiments, the ether polymer comprises structural units represented by formula (BI) and / or formula (BII).
[0021]
[0022] In formula (BI), R 21 and R 22Each independently comprises a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 Including substituted or unsubstituted C1-C5 alkylene groups;
[0023]
[0024] In formula (BII), R 24 To R 27 Each independently comprises a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group, or an ether group, and R 24 To R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy or ether group.
[0025] In some embodiments, the liquid-retaining polymer comprises an ester polymer, wherein the ester polymer is formed into a sheet-like structure; the sheet-like structure is in (T m3 The elastic modulus G' - energy dissipation modulus G” curve was obtained by dynamic frequency scanning test at +20℃. The slope of the elastic modulus G' - energy dissipation modulus G” curve is K2, 1<K2<∞, T m3 ℃ represents the melting temperature of the ester polymer; optionally, 1 < K2 ≤ 100; further optionally, 1 < K2 ≤ 10.
[0026] In some embodiments, the ester polymer comprises structural units represented by formula (CI) and / or formula (CII).
[0027]
[0028] In formula (CI), R 31 R 32 and R 33 Each independently comprises a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl groups, or substituted or unsubstituted C1-C8 hydroxyalkyl groups;
[0029]
[0030] In formula (CII), R 35 Includes substituted or unsubstituted C2-C6 methylene groups; optionally, R 35 Each independently includes substituted or unsubstituted C2-C4 methylene groups.
[0031] In some embodiments, the liquid-retaining polymer comprises an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is formed into a sheet-like structure; the sheet-like structure is in (T m4The elastic modulus G' - energy dissipation modulus G” curve was obtained by dynamic frequency scanning test at +20℃. The slope of the elastic modulus G' - energy dissipation modulus G” curve is K3, 0.8≤K3<∞, T m4 ℃ represents the melting temperature of the aldehyde-ketone polymer; optionally, 0.8 ≤ K3 ≤ 100; further optionally, 0.8 ≤ K3 ≤ 10.
[0032] In some embodiments, the aldehyde-ketone polymer comprises structural units represented by formula (DI) and / or formula (DII).
[0033]
[0034] In formula (DI), R 41 Including single-bonded, substituted, or unsubstituted C1-C6 methylene groups; R 42 Includes hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups;
[0035]
[0036] In formula (DII), R 43 To R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from integers from 0 to 5, and at least one of r and s is selected from a positive integer.
[0037] In some embodiments, the molecular weight of the liquid-retaining polymer is 1.2 × 10⁻⁶. 5 g / mol to 1.0 × 10 6 g / mol.
[0038] In some embodiments, the insulating body includes a substrate, and the polymer layer is disposed on at least one surface of the substrate.
[0039] In some embodiments, the insulating body includes a substrate and a heat-resistant coating, the heat-resistant coating being disposed on at least one surface of the substrate, and the polymer layer being disposed on the surface of the heat-resistant coating opposite to the substrate.
[0040] In some embodiments, the polymer layer further includes heat-resistant particles. The synergistic effect of the heat-resistant particles and the liquid-retaining polymer can further improve the overall heat resistance and ion transport performance of the separator.
[0041] In some embodiments, the basis weight of the polymer layer is 0.5 mg / 1540.25 mm. 2 Up to 5mg / 1540.25mm 2 .
[0042] When the thickness of the polymer layer is within the above range, the overall heat resistance and ion transport performance of the separator can be further improved.
[0043] Secondly, this application proposes a battery cell including a separator as described in any embodiment of the first aspect of this application.
[0044] Thirdly, this application proposes a battery comprising a battery cell as described in any embodiment of the second aspect of this application.
[0045] Fourthly, this application proposes an electrical device including a battery as described in any embodiment of the third aspect of this application. Attached Figure Description
[0046] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0047] Figure 1 This is a schematic diagram of one embodiment of the battery cell of this application.
[0048] Figure 2 yes Figure 1 An exploded view of the implementation method of the battery cell.
[0049] Figure 3 This is a schematic diagram of one embodiment of the battery module of this application.
[0050] Figure 4 This is a schematic diagram of one embodiment of the battery pack of this application.
[0051] Figure 5 yes Figure 4 An exploded view of an embodiment of the battery pack shown.
[0052] Figure 6 This is a schematic diagram of one embodiment of an electrical device that uses the battery cell of this application as a power source.
[0053] The accompanying drawings may not be drawn to scale.
[0054] The annotations in the attached figures are explained as follows:
[0055] 1. Battery pack; 2. Upper casing; 3. Lower casing; 4. Battery module;
[0056] 5. Battery cell; 51. Housing; 52. Electrode assembly;
[0057] 53. Cover plate;
[0058] 6. Electrical appliances. Detailed Implementation
[0059] The following detailed description discloses embodiments of the separator, battery cell, battery, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0060] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0061] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions. Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions.
[0062] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0063] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0064] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0065] In this application, the terms "multiple" or "various" refer to two or more kinds of things.
[0066] The term "alkyl" encompasses both straight-chain and branched alkyl groups. For example, an alkyl group can be C1-C5, C1-C4, C1-C3, or C1-C2 alkyl. In some embodiments, the alkyl group includes methyl, ethyl, propyl, isopropyl, butyl, isobutyl, etc. Additionally, the alkyl group may optionally be substituted. When substituted, the substituent includes a fluorine atom.
[0067] The term "alkoxy group" refers to a group in which an alkyl group is bonded to an oxygen atom by a single bond. For example, an alkoxy group can be a C1-C5 alkoxy group, a C1-C3 alkoxy group, or a C1-C2 alkoxy group. In some embodiments, an alkoxy group may include a methoxy group, an ethoxy group, or a propoxy group. Additionally, an alkoxy group may optionally be substituted.
[0068] The term "halogen atom" refers to fluorine atoms, chlorine atoms, bromine atoms, etc.
[0069] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).
[0070] A battery cell consists of a positive electrode, a negative electrode, a separator, and an electrolyte. The separator is located between the positive and negative electrodes to isolate them. During the charge-discharge cycle of a battery cell, the electrode assembly undergoes volume expansion, especially in the later stages of the cycle when the expansion force is high. This leads to an increase in the distance between the electrodes and the separator, increasing the risk of electrolyte shortage and cell breakage, which may degrade the cycle performance of the battery cell and shorten its cycle life.
[0071] In view of the above problems, this application proposes a separator membrane, which includes a polymer layer comprising an adhesive polymer and a liquid-retaining polymer. The adhesive polymer is coated on the surface of the separator membrane, giving it excellent adhesion and ensuring tight bonding between the electrode and the separator membrane, thereby alleviating liquid shortage caused by increased gaps between the electrodes during battery cycling and improving the cycle performance of the battery cell. On the other hand, when the liquid-retaining polymer comes into contact with the electrolyte, the polymer molecular chains expand and open, allowing the electrolyte to diffuse between the molecular chains. The polymer molecular chains swell and adsorb, forming a three-dimensional connection network between the separator membrane and the electrode. This three-dimensional connection network can adhere to the electrode surface, bonding the separator membrane and the electrode into one unit, further improving the stability of the electrode and separator membrane structure and enhancing the cycle performance of the battery cell. Furthermore, this three-dimensional connection network can lock the electrolyte within the network, maintaining it within the electrode and separator structure, which is beneficial for improving the ion transport interface and facilitating the transport of active ions such as lithium ions and sodium ions, further enhancing the cycle performance of the battery cell.
[0072] Separating membrane
[0073] In a first aspect, embodiments of this application propose an isolation membrane, the isolation membrane comprising an isolation body and a polymer layer disposed on at least one surface of the isolation body, the polymer layer comprising a liquid-retaining polymer, wherein the liquid-retaining polymer is added to a first solvent at 70°C to form a polymer system; the polymer system is allowed to stand at 70°C for 8 hours, and then allowed to stand at 25°C for ≥24 hours, and the polymer system is filtered through a 200-mesh filter to leave a first substance, wherein the mass of the liquid-retaining polymer is q, and the mass of the first substance is m, and the mass of the first substance is m, and the liquid-retaining polymer and the first substance satisfy: 5≤m / q≤1000; and the adhesive force of the isolation membrane is greater than or equal to 10N / m.
[0074] The separator has excellent adhesion, which makes the electrode and the separator bond tightly, thereby alleviating the liquid shortage caused by the increased gap between the electrodes during battery cycling, and thus improving the cycle performance of the cell.
[0075] In some implementations, 10 ≤ m / q ≤ 1000; further optionally, 10 ≤ m / q ≤ 50. For example, m / q can be 5, 10, 20, 25, 28, 30, 32, 35, 40, 50, 80, 100, 200, 500, 1000 or a range of any two of the above values.
[0076] The separator can be made from a substrate and a electrolyte-retaining polymer, etc. Alternatively, the separator can be derived from a single battery cell. The battery cell is disassembled, the separator immersed in the electrolyte is removed, the separator is washed with deionized water, and then vacuum dried at 80°C for 12 hours to obtain the separator, which is then used for separator testing.
[0077] The polymer system undergoes two stages of settling treatment: standing at 70°C for 8 hours and then standing at 25°C for ≥24 hours. During this process, the polymer system partially swells and adsorbs, transforming into a gel state. When the electrolyte comes into contact with the polymer, the polymer molecular chains expand and open, allowing the electrolyte to diffuse between the chains. The polymer molecular chains swell and adsorb, forming a three-dimensional interconnected network between the separator and the electrode. This network adheres to the electrode surface, bonding the separator and electrode together, further enhancing the stability of the electrode and separator structure and thus improving the cycle performance of the battery cell. Furthermore, this three-dimensional interconnected network locks the electrolyte within itself, maintaining it within the electrode and separator structure. This improves the ion transport interface and facilitates the transport of active ions such as lithium and sodium ions, further enhancing the cycle performance of the battery cell.
[0078] For example, based on the mass of the polymer system, the ratio of the mass content of the liquid-retaining polymer to the mass content of the first solvent ranges from 1:100 to 1:10, for example, 3:50.
[0079] For example, the first solvent is the same as or similar to the solvent of the electrolyte, and the first solvent may include at least one of carbonate solvents and ether solvents. For example, carbonate solvents include cyclic carbonate solvents and / or linear carbonate solvents.
[0080] Examples of cyclic carbonate solvents include one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC.
[0081] As examples of linear carbonate solvents, linear carbonate solvents include one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), diphenyl carbonate (DPC), methyl allyl carbonate (MAC), and polycarbonate (VA).
[0082] Examples of ether solvents include one or more of tetrahydrofuran (THF), 2-methyltetrahydrofuran (2me-thf), 1,3-dioxolane (DOL), dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), and diethylene glycol dimethyl ether (DG).
[0083] Optionally, the first solvent may also contain lithium salts and electrolyte additives, such as lithium hexafluorophosphate, vinylene carbonate (VC), and fluorovinylene carbonate (FEC).
[0084] In this application, m / q is also referred to as the precipitation value, which characterizes the ability of the liquid-retaining polymer and solvent to transform into a gel-state substance.
[0085] The first substance mainly includes a gel-state substance formed by a liquid-retaining polymer and a first solvent. In this type of gel-state substance, the molecular structure of the polymer remains basically unchanged.
[0086] In some embodiments, the first substance is dried at 80°C for 12 hours to remove the first solvent from the first substance, and then detected by infrared spectrophotometry (IR) or nuclear magnetic resonance (NMR). After drying, the main component of the first substance is the liquid-retaining polymer described above.
[0087] This application's embodiments, by increasing the temperature, allow the liquid-retaining polymer molecular chains to expand within the safe operating temperature range of the battery cell, promoting mutual attraction and physical bonding between the polymer molecular chains and the electrolyte. At room temperature, the activity of the liquid-retaining polymer molecular chain segments decreases, remaining attached to the surface of the insulating body and locking the electrolyte within the space of the liquid-retaining polymer, forming a gel or gel-like state. This can enhance the transport rate of active ions, such as lithium ions, and improve cycle performance.
[0088] In some embodiments, the adhesive strength of the separator is greater than or equal to 10 N / m; it can be selected from 10 N / m to 30 N / m. When the adhesive strength of the separator is within the above range, the separator has good adhesion performance, which is beneficial to improving the connection stability between the separator and the electrode. During the charge-discharge cycle of the battery cell, it reduces the risk of the distance between the separator and the electrode increasing, thereby allowing the electrode assembly to adsorb a larger amount of electrolyte, which is beneficial to improving cycle performance. For example, the adhesive strength of the separator is 10 N / m, 12 N / m, 15 N / m, 16 N / m, 18 N / m, 20 N / m, 22 N / m, 25 N / m, 28 N / m, 30 N / m, or any combination of two of the above values. The adhesive strength of the separator mainly refers to the adhesive strength on the side with the polymer layer.
[0089] In the embodiments of this application, the adhesive force of the separator is tested using equipment and methods known in the art. For example, the positive electrode, the separator, and the negative electrode are stacked sequentially to form a stacked electrode assembly. The electrode assembly is placed in a hot press machine and hot-pressed at 80°C and 8000N for 120s. Then it is placed in a high-speed rail tensile testing machine. The adhesive force displayed in the high-speed rail tensile testing machine is the adhesive force of the separator.
[0090] In some embodiments, the polymer layer may be formed by spraying a mixture of liquid-retaining polymer and solvent onto the insulating body. The solvent may include at least one of aqueous solvent and oil-based solvent, and the oil-based solvent can be understood as an organic solvent.
[0091] When the solvent includes an aqueous solvent such as water, an adhesive polymer can be added to the mixture to improve the adhesion of the polymer layer. In some embodiments, the adhesive polymer may include one or more of epoxy resins, polyurethanes, silicones, polyimides, polyacrylates, polymethacrylates, and ethyl acetate (VAE) emulsions. These adhesive polymers have good adhesive properties. Optionally, the polyacrylate may include ethyl acrylate.
[0092] In some embodiments, based on the total mass of the polymer layer, the ratio of the mass percentage of the liquid-retaining polymer to the mass percentage of the adhesive polymer is (1 to 9):1. When the mass percentage ratio of the liquid-retaining polymer to the adhesive polymer is within the above range, both the adhesive and gel properties of the polymer layer can be improved. For example, the mass percentage ratio of the liquid-retaining polymer to the adhesive polymer can be 1:1, 2:1, 3:1, 5:1, 6:1, 7:1, 8:1, 9:1, or a range consisting of any two of the above values.
[0093] The particle size of the liquid-retaining polymer may be smaller than that of the adhesive polymer. The polymer layer can be considered to be composed of large adhesive polymer particles with high adhesion and small liquid-retaining polymer particles. The large particles agglomerate to form protrusions, and the polymer layer presents an island-like structure.
[0094] When the solvent includes an oily solvent such as N-methylpyrrolidone (NMP) and / or polyethersulfone, the polymer layer may include an oily solvent and a liquid-retaining polymer, which provides adhesive properties, giving the separator excellent adhesive characteristics, and the resulting polymer layer exhibits a network structure.
[0095] When the polymer layer and electrolyte are in contact, the molecular chains of the electrolyte-retaining polymer expand and adsorb the electrolyte into the chains, forming a three-dimensional cross-linked network structure with the electrode. This allows for rapid transport of active ions at the electrolyte-electrode interface. Furthermore, the introduction of highly adhesive polymers into the three-dimensional cross-linked network structure ensures tight adhesion between the separator and the electrode, reducing problems such as increased spacing between the electrode and separator due to electrode expansion in later stages of cycling. This allows for continuous electrolyte transport along the initial path, reducing the risk of electrolyte bridging caused by expansion during cycling. It also minimizes the risk of lithium plating at the electrode interface, thereby improving the cycle performance of the battery cell.
[0096] The polymer layer in the embodiments of this application can be prepared by the following steps:
[0097] The liquid-retaining polymer and optional adhesive polymer are added to the solvent and mixed to form a mixture system;
[0098] The mixed system is atomized and sprayed onto the surface of the isolation body to form a polymer layer.
[0099] When using water-based solvent atomization spraying, the adhesive polymer can provide excellent adhesion to the release membrane, and the polymer layer may exhibit an island-like structure.
[0100] When using oil-based solvent atomization spraying, the liquid-retaining polymer has a certain adhesive ability, and the adhesive polymer can further increase the adhesive ability, and the polymer layer may present a network structure.
[0101] In some embodiments, the basis weight of the polymer layer is 0.5 mg / 1540.25 mm. 2 Up to 5mg / 1540.25mm 2 .
[0102] When the coating basis weight is within the above range, the ability to form a gel-like substance with the electrolyte can be further enhanced, thereby increasing the liquid absorption rate. Optionally, the coating basis weight of the polymer layer of the separator is 0.5 mg / 1540.25 mm. 2 Up to 3.5mg / 1540.25mm 2 .
[0103] For example, the coating basis weight of the polymer layer of the separator membrane can be 0.5 mg / 1540.25 mm. 2 0.8mg / 1540.25mm 2 1.0mg / 1540.25mm 2 1.2mg / 1540.25mm 2 1.3mg / 1540.25mm 21.5mg / 1540.25mm 2 2.0mg / 1540.25mm 2 2.2mg / 1540.25mm 2 2.5mg / 1540.25mm 2 3mg / 1540.25mm 2 3.5mg / 1540.25mm 2 4mg / 1540.25mm 2 4.5mg / 1540.25mm 2 5mg / 1540.25mm 2 Or a range consisting of any two of the above values.
[0104] In this embodiment, the coating basis weight refers to the coating basis weight of the polymer layer on one side of the release liner, which can be tested using equipment and methods known in the art. For example, it can be measured by cutting the same master roll substrate and release liner into 1540.25mm pieces. 2 Weigh 10 small discs of the separator film and calculate the coating weight of the polymer layer in the separator film.
[0105] In some embodiments, the liquid-retaining polymer may include one or more of fluorinated polymers, ether polymers, ester polymers, and ketone-aldehyde polymers.
[0106] In some embodiments, the liquid-retaining polymer comprises a fluorinated polymer, wherein the crystallinity of the fluorinated polymer, as determined by differential scanning calorimetry, is X. C1 , 0 < X C1 ≤30%; the melting temperature of the fluoropolymer is T m1 Its unit is ℃, 0 < T m1 ≤140.
[0107] Crystallization refers to the process by which atoms, ions, or molecules in a material arrange themselves in a specific spatial order to form an ordered structure. The conformation of polymers during crystallization is determined by both intramolecular and intermolecular factors. Intermolecular forces affect the packing density between molecular chains. Crystallinity X C1 The degree of crystallinity in a material is characterized by differential scanning calorimetry (DSC). Specifically, the testing procedure is as follows: Take 0.5g to 0.8g of sample, place the sample in a crucible, and subject the sample to heating and cooling at a nitrogen atmosphere, with a heating rate of 10℃ / min from the intrinsic temperature of the material (T0). g1 The initial temperature was 20°C lower than the material's intrinsic temperature, and the temperature was increased to the material's intrinsic temperature. m1 The cutoff temperature for the 20°C increase is determined by the actual glass transition temperature T of the material, based on the peak values of heat absorption and release or the transition point during the process. g1and melting temperature T m1 wait.
[0108] Therefore, fluorinated polymers have relatively low crystallinity and melting temperature, which makes the molecular chain arrangement tend to be loose, the interaction force between molecular chains is small, adjacent molecular chains are easily opened, and chain segment movement is achieved through intermolecular rotation, forming a molecular chain structure with high flexibility; and fluorinated polymers and electrolytes in battery cells can form gel-like substances, improving the cycle performance of battery cells.
[0109] For example, the crystallinity X of a fluorinated polymer, measured by differential scanning calorimetry. C1 It can be 5%, 10%, 15%, 20%, 25%, 30%, or a range of any two of the above values.
[0110] For example, the melting temperature of the fluoropolymer can be 10°C, 20°C, 50°C, 70°C, 90°C, 100°C, 120°C, 140°C, or any combination of two of the above values.
[0111] In some embodiments, the glass transition temperature of the fluorinated polymer is T. g1 Its unit is ℃, -150≤T g1 ≤60.
[0112] The glass transition temperature (GLT) is the temperature at which polymer chain segments transition from frozen to mobile. The GLT has a certain influence on the flexibility of polymer molecular chains; the lower the GLT, the better the flexibility of the polymer molecular chains at room temperature, and vice versa. The GLT can be measured using differential scanning calorimetry (DSC). Polymers with relatively low GLTs exhibit better chain segment flexibility, making it easier for adjacent molecular chains to open. For example, the GLT of fluorinated polymers can be -150℃, -120℃, -100℃, -80℃, -60℃, -30℃, 0℃, 30℃, 60℃, or any combination of two of these values.
[0113] In some embodiments, the fluoropolymer includes at least one of the structural units represented by formula (A1) to formula (AIII).
[0114]
[0115] In equations (AI) and (AII), R 11 R 12 R 13 and R 14Each independently comprises a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 R 12 R 13 and R 14 At least one of them contains a fluorine atom.
[0116] In equation (AIII), R 15 Includes single-bonded, substituted or unsubstituted C1-C3 alkyl groups.
[0117] When the above-mentioned groups are substituted, the substituents may include one or more of the following: nitrile (-CN), nitro, sulfonic acid, sulfonyl, amide, carboxyl, ester, and halogen atom. These substituents are high-pressure resistant and are more conducive to stabilizing the polymer structure. The halogen atom may include fluorine, chlorine, bromine, etc. Optionally, the halogen atom may include a fluorine atom.
[0118] In embodiments of this application, the polymer can also be obtained by copolymerizing the above-mentioned structural groups with a small amount of other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers, etc.).
[0119] In some implementations, p is selected from positive integers from 1 to 3.
[0120] In some implementations, n is selected from a positive integer from 1000 to 30000.
[0121] In some implementations, R 11 R 12 R 13 and R 14 Each independently comprises a hydrogen atom, a fluorine atom, a bromine atom, a substituted or unsubstituted C1-C2 alkyl group, or a substituted or unsubstituted C1-C2 alkoxy group; further optionally, R 11 R 12 R 13 and R 14 Each of these atoms independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group, or a perfluoromethoxy group.
[0122] In some embodiments, the fluorinated polymer includes at least one of the structural units shown in formula (AI-1) to formula (AI-11).
[0123]
[0124] In some embodiments, the fluorinated polymer includes at least one of the structural units shown in formula (AII-1) to formula (AII-5).
[0125]
[0126] In some embodiments, the fluorinated polymer includes at least one of the structural units shown in formula (AIII-1) to formula (AIII-3).
[0127]
[0128] For example, the fluorinated polymer includes one or more of the following: perfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene-propylene copolymer (FEP), perfluoroalkoxy polymer (PFA), perfluoropolyether (PFPE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE), and perfluoro(1-butenyl vinyl ether) polymer (CYTOP).
[0129] Optionally, the fluorinated polymer includes one or more of perfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE).
[0130] The aforementioned fluorinated polymers can be derived from one or more of the following monomers: fluorinated cyclohexane, fluorinated vinylidene, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, trifluorochloroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene, and pentafluoropropylene. Optionally, the aforementioned fluorinated polymers can be derived from at least two of the following monomers: fluorinated cyclohexane, fluorinated vinylidene, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, trifluorochloroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene, and pentafluoropropylene.
[0131] The monomers used in the above-mentioned fluorinated polymers are all short-chain monomers, which are conducive to the polymerization to form straight-chain linear structures or short-branched structures. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chains. The molecular chains can fully extend in the electrolyte, which is conducive to the formation of a three-dimensional gel-like substance by the polymer and the electrolyte, and is conducive to further improving the liquid absorption rate.
[0132] In some implementations, n is selected from a positive integer between 5000 and 20000.
[0133] In some embodiments, the molecular weight of the liquid-retaining polymer is 1.2 × 10⁻⁶. 5 g / mol to 1.5 × 10 6g / mol; can be selected as 1.2×10 5 g / mol to 1.0 × 10 6 When the molecular weight of the polymer is within the above range, it ensures that the polymer exhibits a certain degree of solubility in the electrolyte, while being less likely to be completely dissolved and dispersed by the electrolyte. This is beneficial for controlling the distribution and dispersion of the polymer. Furthermore, it can further improve the flexibility between the polymer molecular chains, and the relatively weak interaction forces between the molecular chains facilitate the solvent molecules in the electrolyte to open the molecular chains and enter between the molecular chains, where they are encapsulated. This, in turn, facilitates the smooth and rapid migration of active ions into the active substance through the solvent.
[0134] When the molecular weight of the polymer is within the aforementioned range, it ensures that the polymer exhibits a certain degree of solubility in the electrolyte while being less likely to be completely dissolved and dispersed by the electrolyte. This facilitates the control of the polymer's distribution and dispersion on the surface of the active material. Furthermore, it enhances the flexibility between the polymer's molecular chains, resulting in relatively weaker intermolecular forces. This allows solvent molecules in the electrolyte to open the molecular chains and enter between them, where they are encapsulated. Consequently, it facilitates the smooth and rapid migration of active ions into the active material through the solvent. For example, the molecular weight of the polymer can be 1.2 × 10⁻⁶. 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.
[0135] [Ether polymers]
[0136] In some embodiments, the liquid-retaining polymer comprises an ether polymer, which is formed into a sheet-like structure; the sheet-like structure is in (T m2 The elastic modulus G' - energy dissipation modulus G” curve was obtained by dynamic frequency scanning test at +20℃. The slope of the elastic modulus G' - energy dissipation modulus G” curve is K1, 1<K1<∞, T m2 °C represents the melting temperature of the ether polymer.
[0137] Specifically, the preparation process of the sheet-like structure is as follows: The ether polymer is vacuum dried at 80°C for 12 hours. The dried ether polymer is then hot-pressed into thin sheets using a flat vulcanizing machine, with the hot-pressing temperature set to (T...). m2The temperature is +20℃, the calendering thickness is 1-2 min, the calendering time is 2 min, and the pressure is 8 MPa. After calendering for 2 min, the sample is removed and placed on another vulcanizing machine of the same model for cold pressing at a pressure of 10 MPa. Polymer discs (sheet-like structures) of a fixed size can be obtained using a circular mold with a diameter of 25 mm. For example, the sheet-like structure can be a disc with a thickness of 1-2 mm and a diameter of 25 mm; it can also be prepared according to the sample standard required by the testing equipment.
[0138] According to the conclusions of classical linear viscoelasticity, for polymers, especially linear polymers, the elastic modulus G'-energy dissipation modulus G” curve exhibits frequency dependence in the terminal region (the range approaching the maximum angular velocity), and the longest chain of the polymer plays a role in viscoelastic behavior.
[0139] The specific steps of the dynamic frequency scanning test are as follows: A TA-AR2000EX rotational rheometer (TA Instruments, USA) is used for the dynamic frequency scanning test. The parallel plate has a diameter of 25 mm and a thickness of 0.9 mm. To ensure the test is conducted within the linear springback region, the strain is set at 2% during the dynamic frequency scanning test, and the test temperature is T. m2 +20℃, test frequency sweep range: 500rad / s≤w 2 ≤0.05rad / s, so as to obtain data in the lowest possible frequency range.
[0140] Dynamic frequency scanning tests can characterize the degree of molecular chain entanglement during solid-state melting (molten state). Compared to linear or short-branched structures, long-branched, network, and low-crosslinked structures exhibit high entanglement and deviate from linear end-effector behavior, while ether polymers exhibit solid-state behavior. When the ether polymers of this application meet the above-mentioned range, they can further reduce the molecular chain entanglement state, which is beneficial for the diffusion of solvent molecules between molecular chains in the electrolyte. Furthermore, the ether polymers still maintain a certain degree of molecular chain entanglement, enabling them to form gel-like substances with the electrolyte, thus improving the cycle performance and storage performance of the battery cells.
[0141] In some implementations, 1 < K1 ≤ 100; alternatively, 1 < K1 ≤ 10. For example, K1 can be 1.01, 1.1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000 or a range of any two of the above values.
[0142] In some embodiments, the glass transition temperature of the ether polymer is T. g2 Its unit is ℃, -100≤T g2 ≤50; optionally, -80≤T g2≤30. For example, the glass transition temperature of the ether polymer can be -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range of any two of the above values.
[0143] In some embodiments, the ether polymer comprises structural units represented by formula (BI).
[0144]
[0145] In formula (BI), R 21 and R 22 Each independently comprises a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 This includes substituted or unsubstituted C1-C5 methylene groups.
[0146] In some implementations, R 21 and R 22 Each independently includes a hydrogen atom and a substituted or unsubstituted C1-C2 alkyl group.
[0147] In some implementations, R 23 This includes single-bonded, substituted, or unsubstituted C1-C4 methylene groups.
[0148] For example, the ether polymer includes at least one of the structural units shown in formula (BI-1) to formula (BI-8).
[0149]
[0150] In some embodiments, the ether polymer comprises structural units represented by formula (BII).
[0151]
[0152] In formula (BII), R 24 To R 27 Each independently comprises a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group, or an ether group, and R 24 To R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy or ether group.
[0153] In some implementations, R 24 To R 27 Each independently comprises a hydrogen atom, a substituted or unsubstituted C1-C2 alkyl group, a substituted or unsubstituted C1-C2 alkoxy group, or an ether group, and R 24 To R 27At least one of them contains a substituted or unsubstituted C1-C2 alkoxy or ether group.
[0154] In some embodiments, the ether polymer includes at least one of the structural units shown in formula (BII-1) to formula (BII-7).
[0155]
[0156] The monomers used in the above-mentioned ether polymers are polycyclic rings, such as six-membered rings or shorter-chain monomers, which are conducive to the polymerization to form a high content of -O- structures. This type of structure has a low degree of entanglement, which is beneficial to improving the flexibility of the molecular chain. The molecular chain can fully extend in the electrolyte and easily form a gel with the electrolyte, thereby improving the cycle performance and storage performance of the battery cell.
[0157] The polymers described above are merely examples of structural groups in the main molecular chains. In the embodiments of this application, the polymers may also be obtained by copolymerizing the above structural groups with a small amount of other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers, etc.).
[0158] When the above groups are substituted, the substituents may include one or more of the following: nitrile (-CN), nitro, sulfonic acid, sulfonyl, amide, carboxyl, ester, and halogen atom. These substituents are high-pressure resistant and more conducive to stabilizing the polymer structure. Halogen atoms may include fluorine, chlorine, bromine, etc.
[0159] In some implementations, n is selected from a positive integer from 1500 to 25000.
[0160] Optionally, n is selected from a positive integer between 3000 and 18000.
[0161] In some embodiments, the polymer has a molecular weight of 1.2 × 10⁻⁶. 5 g / mol to 1.0 × 10 6 g / mol.
[0162] For example, the molecular weight of the polymer can be 1.2 × 10⁻⁶. 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol or a range consisting of any two of the above values.
[0163] [Ester polymers]
[0164] In some embodiments, the liquid-retaining polymer comprises an ester polymer, wherein the ester polymer is formed into a sheet-like structure; the sheet-like structure is in (T m3 The elastic modulus G' - energy dissipation modulus G” curve was obtained by dynamic frequency scanning test at +20℃. The slope of the elastic modulus G' - energy dissipation modulus G” curve is K2, 1<K2<∞, T m3 °C represents the melting temperature of the ester polymer.
[0165] When the ester polymers of the embodiments of this application meet the above-mentioned range, the molecular chain entanglement state can be further reduced, which is beneficial to the diffusion of solvent molecules in the electrolyte between molecular chains; and the ether polymers still maintain a certain molecular chain entanglement state, which can form a gel-like substance with the electrolyte, thereby increasing the liquid absorption rate and improving the cycle performance and storage performance of the battery cell.
[0166] In some implementations, 1 < K2 ≤ 100; alternatively, 1 < K2 ≤ 10.
[0167] For example, K2 can be 1.01, 1.1, 1.2, 1.5, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000 or a range of any two of the above values.
[0168] In some embodiments, the glass transition temperature of the ester polymer is T. g3 Its unit is ℃, -100≤T g3 ≤50; optionally, -80≤T g3 ≤30.
[0169] For example, the glass transition temperature of the ester polymer can be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range of any two of the above values.
[0170] In some embodiments, the ester polymer comprises structural units represented by formula (CI).
[0171]
[0172] In formula (CI), R 31 R 32 and R 33 Each independently comprises a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Includes substituted or unsubstituted C1-C8 alkyl groups, or substituted or unsubstituted C1-C8 hydroxyalkyl groups; optionally, R 34This includes substituted or unsubstituted C1-C6 alkyl groups, or substituted or unsubstituted C1-C6 hydroxyalkyl groups.
[0173] Optionally, R 31 This includes hydrogen atoms, or substituted or unsubstituted methyl groups.
[0174] Optionally, R 32 and R 33 Each of them independently contains a hydrogen atom.
[0175] Optionally, R 34 This includes substituted or unsubstituted C1-C4 alkyl groups, or substituted or unsubstituted C1-C4 hydroxyalkyl groups.
[0176] Exemplarily, the ester polymer includes at least one of the structural units shown in formula (CI-1) to formula (CI-15).
[0177]
[0178]
[0179] In some embodiments, the ester polymer comprises structural units represented by formula (CII).
[0180]
[0181] In formula (CII), R 35 This includes substituted or unsubstituted C2-C6 methylene groups.
[0182] Optionally, R 35 Each independently includes substituted or unsubstituted C2-C4 methylene groups.
[0183] For example, the ester polymer includes at least one of the structural units shown in formula (CII-1) to formula (CII-5).
[0184]
[0185] The aforementioned ester polymers have a low degree of molecular chain entanglement, which is beneficial to improving the flexibility of the molecular chains. The molecular chains can fully extend in the electrolyte and easily form a gel-like substance with the electrolyte.
[0186] The polymers described above are merely examples of structural groups in the main molecular chains. In the embodiments of this application, the polymers may also be obtained by copolymerizing the above structural groups with other types of structural groups (such as olefin structural units, acrylonitrile structural units, maleic anhydride and other monomers with functional groups).
[0187] When the above groups are substituted, the substituents may include one or more of the following: nitrile, nitro, sulfonyl, carboxyl, ester, chlorine, fluorine, and bromine. These substituents are high-pressure resistant and are more conducive to stabilizing the polymer structure.
[0188] In some implementations, n is selected from a positive integer from 800 to 20000.
[0189] Optionally, n is selected from a positive integer between 1000 and 15000.
[0190] In some embodiments, the polymer has a molecular weight of 1.2 × 10⁻⁶. 5 g / mol to 1.0 × 10 6 g / mol.
[0191] For example, the molecular weight of the polymer can be 1.2 × 10⁻⁶. 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.
[0192] [Ketone-aldehyde polymers]
[0193] In some embodiments, the liquid-retaining polymer comprises an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is formed into a sheet-like structure; the sheet-like structure is in (T m4 The elastic modulus G' - energy dissipation modulus G” curve was obtained by dynamic frequency scanning test at +20℃. The slope of the elastic modulus G' - energy dissipation modulus G” curve is K3, 0.8≤K3<∞, T m4 °C represents the melting temperature of the aldehyde-ketone polymer.
[0194] In some implementations, 0.8 ≤ K3 ≤ 100; alternatively, 0.8 ≤ K3 ≤ 10.
[0195] For example, K3 can be 0.8, 0.9, 1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000 or a range of any two of the above values.
[0196] In some embodiments, the glass transition temperature of the aldehyde-ketone polymer is T. g4 Its unit is ℃, -100≤T g4 ≤50; optionally, -80≤T g4 ≤30.
[0197] For example, the glass transition temperature of the aldehyde-ketone polymer can be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range of any two of the above values.
[0198] In some embodiments, the aldehyde-ketone polymer comprises structural units represented by formula (DI).
[0199]
[0200] In formula (DI), R 41 Including single-bonded, substituted, or unsubstituted C1-C6 methylene groups; R 42 Includes hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups;
[0201] Optionally, R 41 Including single-bonded, substituted, or unsubstituted C1-C2 methylene groups;
[0202] Optionally, R 42 Includes hydrogen atoms, substituted or unsubstituted C1-C3 alkyl groups.
[0203] In the embodiments of this application, a single bond indicates that the group does not exist, and the atoms on both sides of the group are connected by a single bond, such as R. 41 A single bond, representing R 41 The carbon atoms on both sides are connected by single bonds.
[0204] Exemplarily, the aldehyde-ketone polymer includes at least one of the structural units shown in formula (DI-1) to formula (DI-6).
[0205]
[0206]
[0207] Exemplarily, the aldehyde-ketone polymer comprises the structural unit shown in formula (DII).
[0208]
[0209] In formula (DII), R 43 To R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from integers from 0 to 5, and at least one of r and s is selected from a positive integer; optionally, R 43 To R 46Each of these components independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.
[0210] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units shown in formula (DII-1) to formula (DII-4).
[0211]
[0212] The molecular chains of the aforementioned aldehyde-ketone polymers have a low degree of entanglement, which is beneficial to improving the flexibility of the molecular chains. The molecular chains can fully extend in the electrolyte, which is conducive to forming a gel-like substance with the electrolyte.
[0213] The polymers described above are merely examples of structural groups in the main molecular chains. In the embodiments of this application, the polymers can also be obtained by copolymerizing the above structural groups with other types of structural groups (such as olefin structural units, enol structural units, acrylonitrile structural units, etc.).
[0214] When the above groups are substituted, the substituents may include one or more of the following: nitrile (-CN), nitro, sulfonyl, carboxyl, ester, chlorine, fluorine, and bromine. These substituents are high-pressure resistant and are more conducive to stabilizing the polymer structure.
[0215] In some implementations, n is selected from a positive integer from 500 to 15000.
[0216] Optionally, n is selected from a positive integer between 500 and 10000.
[0217] In some embodiments, the polymer has a molecular weight of 1.2 × 10⁻⁶. 5 g / mol to 1.0 × 10 6 g / mol.
[0218] For example, the molecular weight of the polymer can be 1.2 × 10⁻⁶. 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.0×10 6 g / mol or a range consisting of any two of the above values.
[0219] The relevant parameters of the liquid-retaining polymer in the embodiments of this application can be detected using the following methods:
[0220] The functional groups of the liquid-retaining polymer in this embodiment can be detected using infrared spectrophotometry (IR). Specifically, the liquid-retaining polymer is tested using a Thermo Nicolet Nexus 670 attenuated total reflectance Fourier transform infrared spectrometer (FTIR-ATR), and then tested according to standard GB / T6040-2002. The test range is 600–4000 cm⁻¹ using the ATR method. -1 Repeatability: ±2cm -1 Resolution: better than 4cm -1 ; Transmission depth 0.2~0.6μm.
[0221] The structure of the liquid-retaining polymer in this embodiment can be determined by nuclear magnetic resonance (NMR). Specifically, 1H NMR and 13C NMR are performed on a Varian Mercury Plus-400 NMR spectrometer at a test temperature of 20°C, with TMS as an internal standard, CDCl3 as a solvent, and a proton resonance frequency of 400 MHz.
[0222] The polymer monomer type of the liquid-retaining polymer in this embodiment (especially suitable for monomers with a small proportion in the polymer) can be determined by pyrolysis-gas chromatography-mass spectrometry. The specific testing steps are as follows: Accurately weigh 0.5 mg of sample into a sample cup, fix it to the injection rod, and then insert it into the pyrolyzer installed near the GC (gas chromatography) injection port. After the pyrolyzer temperature reaches the set temperature, press the injection button. The sample cup will fall rapidly into the core of the pyrolysis furnace through free fall. In the inert gas N2 atmosphere, the volatile components will instantly vaporize and be carried into the gas chromatography column by the carrier gas for separation. Finally, it will be detected by flame ionization detector (FID) or mass spectrometer (MS) to obtain a gas chromatogram or total ion chromatogram.
[0223] The molecular weight of the liquid-retaining polymer in this application embodiment has a meaning known in the art and can be determined using commonly used equipment and methods in the art. It can be tested by gel permeation chromatography (GPC). The specific test steps are as follows: take an appropriate amount of the sample to be tested (the sample concentration should be 8%-12% opacity), add 20 ml of deionized water, and simultaneously incubate for 5 min (53 kHz / 120 W) to ensure that the sample is completely dispersed. Then, the sample is measured according to the standard GB / T19077-2016 / ISO 13320:2009.
[0224] Alternatively, a multi-angle laser scattering (MALLS) instrument can be used for testing. Specifically, an instrument combining a GPC with a Dawn Heleos II multi-angle laser light scattering device, an Optilab T-rEX refractive index (RI) detector, and a Visco Star II viscometer (Wyatt Technology Corporation, USA) is employed. Tests are conducted at 30°C using tetrahydrofuran as the mobile phase at a flow rate of 1.0 ml / min. SEC-SAMLL data are processed using the commercial software ASTRA6 to obtain molecular weight parameters.
[0225] In this embodiment, the separator membrane includes a separator body and a polymer layer. The polymer layer is disposed on at least one surface of the separator body, meaning that the polymer layer can be disposed on one or both surfaces of the separator body. Since the separator body has various structural forms, the polymer layer correspondingly has various placement forms. The liquid-retaining polymer can be dispersed in a solvent to form a polymer mixture system, which is then coated onto the separator body using coating processes such as atomization spraying or gravure coating.
[0226] In some embodiments, the isolation body includes a substrate, and a polymer layer is disposed on at least one surface of the substrate.
[0227] In other embodiments, the insulating body includes a substrate and a heat-resistant coating, the heat-resistant coating being disposed on at least one surface of the substrate, and the polymer layer being disposed on the surface of the heat-resistant coating opposite to the substrate. It is understood that the heat-resistant coating may be disposed on one or both surfaces of the substrate.
[0228] The embodiments of this application do not impose particular limitations on the material of the substrate. Any known substrate with good chemical and mechanical stability can be selected. For example, the substrate may include at least one of porous polyolefin-based resin membranes (e.g., polyethylene, polypropylene, polyvinylidene fluoride), porous glass fiber, and porous nonwoven fabric. The substrate may be a single-layer film or a multi-layer composite film. When the substrate is a multi-layer composite film, the materials of each layer may be the same or different.
[0229] In some embodiments, the porosity of the substrate is greater than or equal to 25%; optionally, it is between 25% and 50%. When the porosity of the substrate is within the above range, the air permeability of the substrate can be improved, which is beneficial to the migration of active ions. Furthermore, due to the relatively small porosity, the mechanical properties of the substrate can also be improved, and it provides good support for the polymer layer.
[0230] In some embodiments, the thickness of the substrate may be less than or equal to 16 μm, and may be selected from 5 μm to 12 μm. Exemplarily, the thickness of the substrate may be 1 μm, 2 μm, 3 μm, 5 μm, 10 μm, 12 μm, 15 μm, 16 μm, or a range of any two of the above values.
[0231] The heat-resistant coating may include heat-resistant particles. In some embodiments, the heat-resistant particles include at least one of inorganic and organic particles. By incorporating heat-resistant particles, the heat resistance of the separator can be improved.
[0232] In some embodiments, the mass percentage of inorganic particles in the heat-resistant coating is ≤30%. Exemplarily, the mass percentage of inorganic particles in the heat-resistant coating is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, or a range of any two of the above values.
[0233] Inorganic particles may include at least one of the following: inorganic particles having a dielectric constant of 5 or higher, inorganic particles having the ability to transport active ions, and inorganic particles capable of undergoing electrochemical oxidation and reduction.
[0234] In some embodiments, inorganic particles having a dielectric constant of 5 or higher may include boehmite (γ-AlOOH), alumina (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), and silicon oxides (SiO2). x (0<x≤2), Tin dioxide (SnO2), Titanium oxide (TiO2), Calcium oxide (CaO), Zinc oxide (ZnO), Zirconia (ZrO2), Yttrium oxide (Y2O3), Nickel oxide (NiO), Hafnium dioxide (HfO2), Cerium oxide (CeO2), Zirconium titanate (ZrTiO3), Barium titanate (BaTiO3), Magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0 < m < 1, 0 < n < 1) and Pb (Mg3Nb) 2 / 3 At least one of O3-PbTiO3 (abbreviated as PMN-PT).
[0235] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4) and lithium titanium phosphate (Li... x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium titanium aluminum phosphate (Li x Al yTi z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass-like materials (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS2 type glass (Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4) and P2S5 type glass (Li x P y S z At least one of the following: 0 < x < 3, 0 < y < 3, 0 < z < 7.
[0236] In some embodiments, the inorganic particles capable of undergoing electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates with an olivine structure, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.
[0237] In some embodiments, the heat-resistant coating may also include other organic particles, such as at least one of polystyrene, polyethylene, polyimide, melamine resin, phenolic resin, polypropylene, polyester (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), polyphenylene sulfide, polyarylamide, polyamide-imide, polyimide, copolymers of butyl acrylate and ethyl methacrylate, and mixtures thereof.
[0238] In some embodiments, the heat-resistant coating may also include an adhesive. As an example, the adhesive may include at least one of aqueous acrylic resins (e.g., homopolymers of acrylic acid, methacrylic acid, sodium acrylate monomers, or copolymers with other comonomers), polyvinyl alcohol (PVA), isobutylene-maleic anhydride copolymers, and polyacrylamide.
[0239] In some embodiments, the thickness of the heat-resistant coating can be ≤4μm. This helps to improve the energy density of the battery cell. In the embodiments of this application, the thickness of the heat-resistant coating refers to the thickness of the heat-resistant coating located on one side of the substrate. Exemplarily, the thickness of the heat-resistant coating can be 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, or any range of two of the above values.
[0240] In some embodiments, the polymer layer may further include heat-resistant particles. The heat-resistant particles and the liquid-retaining polymer work synergistically to further improve the overall heat resistance and ion transport performance of the separator. The liquid-retaining polymer and the heat-resistant particles can be dispersed in a solvent to form a polymer mixture system, which is then coated onto the separator body using coating processes such as atomization spraying or gravure coating.
[0241] In some embodiments, the thickness of the polymer layer can be from 0.5 μm to 3.0 μm; optionally, it can be from 1.0 μm to 2.0 μm. When the thickness of the polymer layer is within the above range, the overall heat resistance and ion transport performance of the separator can be further improved. For example, the thickness of the polymer layer can be 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.3 μm, 2.5 μm, 2.8 μm, 3.0 μm, or any combination of two of the above values.
[0242] battery cell
[0243] Secondly, embodiments of this application provide a battery cell, the battery cell including an electrode assembly and an electrolyte, the electrode assembly including a positive electrode, a negative electrode and a separator, the separator being disposed between the positive electrode and the negative electrode, the separator including the separator as described in any embodiment of the first aspect of this application.
[0244] [Positive electrode plate]
[0245] The positive electrode includes a positive current collector and a layer of positive active material disposed on at least one surface of the positive current collector.
[0246] As an example, the positive current collector has two surfaces opposite each other in its thickness direction, and the positive active material layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0247] The positive electrode active material layer includes a positive electrode active material, which may be a positive electrode active material known in the art for use in battery cells. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphate compounds, lithium-containing transition metal oxides, sodium-containing phosphate compounds, and sodium-containing transition metal oxides.
[0248] For example, the general formula of olivine-type phosphate active substances (containing lithium phosphate compounds) is: Li x A y Me a M b P 1-c X c Y z Wherein, 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; Y includes one or more of O and F. Specifically, olivine-type phosphate active substances include one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0249] For example, lithium transition metal oxides (layered materials such as ternary, lithium nickel oxide / sodium, lithium cobalt oxide / sodium, lithium manganese oxide / sodium, lithium-rich layered and rock salt phase layered materials, etc.). The general formula for layered cathode active materials is: Li x A y Ni a Co b Mn c M (1-a-b-c) Y z Wherein, 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A includes one or more of Na, K, and Mg; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y includes one or more of O and F. Optionally, y=0. Specifically, the layered structure positive electrode active material may include lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium manganese oxide (LMO), and LiNi. 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 One or more of O2 (NCM811) and NCA.
[0250] In some embodiments, the positive current collector may be a metal foil or a composite current collector. Examples of metal foils include aluminum foil or aluminum alloy foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. Examples of the metal material include one or more combinations selected from aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. The polymer substrate may include one or more combinations selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0251] In some embodiments, the positive electrode active material layer may optionally include a positive electrode conductive agent. This application does not impose particular limitations on the type of positive electrode conductive agent. As an example, the positive electrode conductive agent includes one or more combinations selected from superconducting carbon, conductive carbon black, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is less than 5% based on the total mass of the positive electrode active material layer.
[0252] In some embodiments, the positive electrode active material layer may optionally include a positive electrode binder. This application does not impose particular limitations on the type of positive electrode binder. As an example, the positive electrode binder may include one or more combinations selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins. In some embodiments, the mass percentage of the positive electrode binder is less than 5% based on the total mass of the positive electrode active material layer. The positive electrode binder has a higher crystallinity than the fluorinated polymers of this application. The positive electrode binder has a higher melting temperature than the fluorinated polymers of this application.
[0253] The positive electrode active material layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, followed by drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder, and any other components in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP), but is not limited to it. Of course, the preparation of the positive electrode sheet is not limited to the above methods; the preparation methods described above can also be used.
[0254] [Negative electrode plate]
[0255] In some embodiments, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector and including a negative active material.
[0256] For example, the negative electrode current collector has two surfaces opposite each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0257] The negative electrode active material may be any negative electrode active material known in the art for use in battery cells. As an example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy materials. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy materials.
[0258] In some embodiments, the negative electrode active material layer may optionally include a negative electrode conductive agent. This application does not impose particular limitations on the type of negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one selected from superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5% based on the total mass of the negative electrode active material layer.
[0259] In some embodiments, the negative electrode active material layer may optionally include a negative electrode binder. This application does not impose particular limitations on the type of negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder is ≤5% based on the total mass of the negative electrode active material layer.
[0260] In some embodiments, the negative electrode active material layer may optionally include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc. In some embodiments, the mass percentage of the other additives is ≤2% based on the total mass of the negative electrode active material layer.
[0261] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymeric material substrate and a metal material layer formed on at least one surface of the polymeric material substrate. As an example, the metal material may include at least one of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. As an example, the polymeric material substrate may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0262] The negative electrode active material layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, followed by drying and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional additives in a solvent and stirring until homogeneous. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited to these. Of course, the preparation of the negative electrode sheet is not limited to the above method; the preparation methods described above can also be used.
[0263] The negative electrode sheet does not exclude other additional functional layers besides the negative electrode active material layer. For example, in some embodiments, the negative electrode sheet of this application further includes a conductive undercoat (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode sheet of this application further includes a protective layer covering the surface of the negative electrode active material layer.
[0264] [Electrolytes]
[0265] During the charging and discharging process of a single battery cell, active ions repeatedly insert and extract between the positive and negative electrode plates, while the electrolyte acts as a conductor for these active ions. This application does not impose any particular restrictions on the type of electrolyte; it can be selected according to actual needs.
[0266] The electrolyte comprises an electrolyte salt and a solvent. The types of electrolyte salt and solvent are not specifically limited and can be selected according to actual needs.
[0267] When the battery cell of this application is a lithium-ion battery, as an example, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).
[0268] When the battery cell of this application is a sodium-ion battery, as an example, the electrolyte salt may include, but is not limited to, at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalate borate (NaDFOB), sodium dioxalate borate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorodioxalate phosphate (NaDFOP), and sodium tetrafluorooxalate phosphate (NaTFOP).
[0269] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl ester carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0270] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0271] In some embodiments, the positive electrode, the separator, and the negative electrode can be fabricated into an electrode assembly using a winding process and / or a stacking process.
[0272] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.
[0273] In some embodiments, the outer packaging of the battery cell can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a soft package, such as a pouch. The material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0274] In some implementations, the positive electrode, separator, and negative electrode can be fabricated into an electrode assembly using a winding or stacking process.
[0275] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. Figure 1 The example shown is a square-structured battery cell 5.
[0276] In some embodiments, such as Figure 1 and Figure 2 As shown, the outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, negative electrode sheet, and separator may be formed into an electrode assembly 52 through a winding process or a stacking process. The electrode assembly 52 is encapsulated in the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The number of electrode assemblies 52 contained in a single battery cell 5 may be one or more, and can be adjusted according to requirements.
[0277] The method for preparing the battery cell of this application is well known. In some embodiments, a positive electrode, a separator, a negative electrode, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode, separator, and negative electrode can be formed into an electrode assembly through a winding process or a stacking process. The electrode assembly is placed in an outer packaging, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping processes, a battery cell is obtained.
[0278] In some embodiments of this application, the battery cells according to this application can be assembled into a battery module. The number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0279] Figure 3 This is a schematic diagram of battery module 4 as an example. Figure 3As shown, in battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.
[0280] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0281] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0282] Both battery module 4 and battery pack can be used as specific examples of batteries in the embodiments of this application.
[0283] Figure 4 and Figure 5 This is a schematic diagram of battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3. The upper body 2 covers the lower body 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0284] Electrical appliances
[0285] Thirdly, this application provides an electrical device, which includes at least one of the battery cell, battery module, and battery pack described in this application. The battery cell, battery module, and battery pack can be used as the power source for the electrical device or as the energy storage unit of the electrical device. The electrical device can be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0286] Electrical devices can be equipped with individual battery cells, battery modules, or battery packs depending on their usage requirements. Figure 6 This is a schematic diagram of an example electrical device. The electrical device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of this electrical device, a battery pack 1 or a battery module can be used. Another example electrical device could be a mobile phone, tablet, laptop, etc. These devices typically require a slim and lightweight design, and can use individual battery cells as their power source.
[0287] Example
[0288] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0289] Example 1: Preparation of Lithium-ion Batteries
[0290] (1) Preparation of the positive electrode sheet:
[0291] Aluminum foil with a thickness of 12μm was used as the positive electrode current collector.
[0292] LiNi, the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (NCM622), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are thoroughly mixed in an appropriate amount of N-methylpyrrolidone (NMP) to prepare a positive electrode slurry. The mass ratio of NCM622, conductive carbon black, and PVDF in the positive electrode slurry is 97.5:1.4:1.1. The positive electrode slurry is coated onto a current collector aluminum foil and vacuum dried at 100°C, followed by cold pressing. Then, it is trimmed, cut into sheets, slit, and dried under vacuum at 85°C for 4 hours to produce the positive electrode sheet.
[0293] (2) Preparation of negative electrode sheet:
[0294] A copper foil with a thickness of 8μm was used as the negative electrode current collector.
[0295] Artificial graphite (negative electrode active material), carbon black (conductive agent), styrene-butadiene rubber (SBR) (binder), and sodium carboxymethyl cellulose (CMC) (thickener) were mixed evenly in a weight ratio of 97.4:2:0.5:0.1 and then added to deionized water to prepare a negative electrode slurry. The negative electrode slurry was coated onto a copper foil current collector and dried at 85°C. Then, it was cold-pressed, trimmed, cut into sheets, and slit. Finally, it was dried under vacuum at 120°C for 12 hours to prepare the negative electrode sheet.
[0296] (3) Preparation of electrolyte:
[0297] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent. Then, lithium salt LiPF6 is mixed with the mixed solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0298] (4) Preparation of the separating membrane
[0299] A 7μm polyethylene film (PE) was used as the substrate.
[0300] An adhesive polymer (ethyl polyacrylate) and a liquid-retaining polymer were dispersed in dimethyl carbonate (DMC) solvent to form a mixture. This mixture was then atomized and sprayed onto both surfaces of a polyethylene film to form polymer layers. Water was used as the atomizing solvent, and the mass content of the adhesive polymer (ethyl polyacrylate) and the liquid-retaining polymer in the mixture was 1%.
[0301] (5) Preparation of lithium-ion batteries:
[0302] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator acting as a separator between the positive and negative electrodes. The electrode assembly is then wound up. The electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a lithium-ion battery is obtained.
[0303] Comparative Example 1
[0304] A lithium-ion battery was prepared using a method similar to that of Example 1, except that the separator in Comparative Example 1 was a 7 μm polyethylene film (PE).
[0305] Comparative Example 2
[0306] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 is that the liquid-retaining polymer of the separator in Comparative Example 2 was changed.
[0307] Examples 1-2 to Examples 1-5
[0308] Lithium-ion batteries were prepared using a method similar to that of Example 1. The difference from Example 1 was that the amount of adhesive polymer added to the polymer layer of the separator in Examples 1-2 to 1-6 was adjusted.
[0309] Examples 2-1 to 2-3
[0310] Lithium-ion batteries were prepared using a method similar to that of Example 1. The difference from Example 1 is that the type of liquid-retaining polymer was adjusted in the polymer layer of the separator in Examples 2-1 to 2-3.
[0311] Examples 3-1 to 3-5
[0312] Lithium-ion batteries were prepared using a method similar to that of Example 1. The difference from Example 1 is that the coating weight of the separator in Examples 3-1 to 3-5 was adjusted.
[0313] Example 4-1
[0314] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference between Example 4-1 and Example 4-1 is that the placement of the polymer layer in the separator was adjusted. Specifically, the preparation steps of the separator included:
[0315] A 7μm polyethylene film (PE) was used as the substrate for the release liner;
[0316] Silicon oxide particles and aqueous solution-type polyacrylic acid adhesive polymer are mixed evenly in an appropriate amount of deionized water at a mass ratio of 20:80 to obtain a coating slurry.
[0317] The prepared coating slurry is applied to two surfaces of the PE substrate using a coating machine to form a heat-resistant coating.
[0318] A liquid-retaining polymer and an adhesive polymer are dispersed in dimethyl carbonate (DMC) solvent to form a mixed system. The mixed system is then atomized and sprayed onto the surface of a heat-resistant coating to form a polymer layer, thereby obtaining a release film.
[0319] The data for the examples and comparative examples are shown in Table 1.
[0320] Test section
[0321] 1. Lithium-ion battery performance test (25-minute fast charge cycle performance)
[0322] At 25°C, the lithium-ion battery was charged at a 3C rate and discharged at a 1C rate to perform a full charge-discharge cycle test until the capacity of the lithium-ion battery decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0323] 2. Adhesion test of the release liner
[0324] The positive and negative electrode sheets and the separator are stacked into a stack, which consists of a negative electrode sheet, a separator, and a positive electrode sheet. This device containing the electrode sheet and separator is placed in a hot press and hot-pressed at 80°C and 8000N for 120 seconds.
[0325] The hot-pressed electrode and separator are placed in a high-speed rail tensile testing machine. The adhesion force between the electrode and the separator is expressed as the adhesion force of the separator.
[0326] Test Results
[0327] The test results are shown in Table 1.
[0328] Table 1
[0329]
[0330]
[0331] In Table 1, 88% vinyl ethyl ether refers to the total molar amount of vinyl ethyl ether and vinyl acetate, with a molar percentage content of 88% for vinyl ethyl ether. The liquid-retaining polymer in Example 2-1 has a crystallinity of 10% and a melting temperature of 110°C.
[0332] Compared to Comparative Example 1, the present invention improves the cycle performance of lithium-ion batteries by adding the liquid-retaining polymer of the present application to the separator. Compared to Comparative Example 1, the present invention has a polymer layer on the surface of the separator, which is in contact with the electrolyte. The polymer molecular chains extend and open, allowing the electrolyte to diffuse between the molecular chains, forming a three-dimensional interconnected interface between the separator and the electrode. The introduction of the liquid-retaining polymer creates a uniform high wetting point between the separator and the electrode, uniformly improving the wetting performance of both, thereby increasing the liquid absorption rate of the separator and the electrode, and thus improving the cycle performance of the battery cell. Furthermore, the introduction of an adhesive polymer into the polymer layer further improves the interfacial adhesion, resulting in high adhesion between the separator and the electrode, making their connection more stable. This can alleviate the expansion of the electrode assembly to a certain extent, further improving the cycle performance of the battery cell.
[0333] Although this application has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of this application. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no structural conflict. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A separating membrane, comprising: Isolate the main body; A polymer layer disposed on at least one surface of the insulating body, the polymer layer comprising a liquid-retaining polymer. in, The liquid-retaining polymer is added to a first solvent at 70°C to form a polymer system; The polymer system was allowed to stand at 70°C for 8 hours, and then at 25°C for ≥24 hours. After filtering the polymer system through a 200-mesh filter, the remaining substance was the first component. in, The mass of the liquid-retaining polymer is q, and its unit is g; The mass of the first substance is m, and its unit is g; The liquid-retaining polymer and the first substance satisfy the following condition: 5 ≤ m / q ≤ 50; The adhesive strength of the isolation membrane is greater than or equal to 10 N / m.
2. The separator according to claim 1, wherein, The adhesive strength of the isolation membrane is 10 N / m to 30 N / m.
3. The separator according to claim 1 or 2, wherein, The polymer layer includes an adhesive polymer, which includes one or more of epoxy resins, polyurethanes, silicones, polyimides, polyacrylates, polymethacrylates, and ethyl acetates.
4. The separator according to claim 3, wherein, Based on the total mass of the polymer layer, the ratio of the mass percentage of the liquid-retaining polymer to the mass percentage of the adhesive polymer is (1 to 9):
1.
5. The separator membrane according to claim 1, wherein, The liquid-retaining polymer includes fluoropolymers; The crystallinity of the fluorinated polymer, as determined by differential scanning calorimetry, is Xc1, where 0 < Xc1 ≤ 30%. The melting temperature of the fluoropolymer is T. m1 Its unit is ℃, 0 < T m1 ≤140.
6. The separator according to claim 5, wherein, The glass transition temperature of the fluoropolymer is T. g1 Its unit is ℃, -150≤T g1 ≤60.
7. The separator according to claim 5 or 6, wherein, The fluoropolymer includes at least one of the structural units shown in formula (A1) to formula (AIII). AI (Artificial Intelligence) Formula (AII), In equations (AI) and (AII), R 11 R 12 R 13 and R 14 Each independently comprises a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 R 12 R 13 and R 14 At least one of them contains a fluorine atom; Formula (AIII); In equation (AIII), R 15 Includes single-bonded, substituted or unsubstituted C1-C3 alkyl groups; p is a positive integer selected from 1 to 3; n is a positive integer selected from 1000 to 30000.
8. The separator membrane according to claim 1, wherein, The liquid-retaining polymer further includes an ether polymer, wherein the ether polymer is formed into a sheet-like structure; the sheet-like structure is in (T m2 The elastic modulus G' - energy dissipation modulus G” curve was obtained by dynamic frequency scanning test at +20℃. The slope of the elastic modulus G' - energy dissipation modulus G” curve is K1, 1 < K1 < ∞, T m2 °C represents the melting temperature of the ether polymer.
9. The separator according to claim 8, wherein, 1<K1≤100。 10. The separator according to claim 9, wherein, 1<K1≤10。 11. The separator membrane according to claim 8, wherein, The ether polymers include structural units represented by formula (BI) and / or structural units represented by formula (BII). Formula (BI); In formula (BI), R 21 and R 22 Each independently comprises a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 Including substituted or unsubstituted C1-C5 alkylene groups; Formula (BII); In formula (BII), R 24 To R 27 Each independently comprises a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group, or an ether group, and R 24 To R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy or ether group.
12. The separator according to claim 1, wherein, The liquid-retaining polymer includes an ester polymer, wherein the ester polymer is formed into a sheet-like structure; the sheet-like structure is in (T m3 The elastic modulus G' - energy dissipation modulus G” curve was obtained by dynamic frequency scanning test at +20℃. The slope of the elastic modulus G' - energy dissipation modulus G” curve is K2, 1 < K2 < ∞, T m3 °C represents the melting temperature of the ester polymer.
13. The separator membrane according to claim 12, wherein, 1<K2≤100。 14. The separator according to claim 13, wherein, 1<K2≤10。 15. The separator according to claim 12, wherein, The ester polymers include structural units represented by formula (CI) and / or structural units represented by formula (CII). Formula (CI); In formula (CI), R 31 R 32 and R 33 Each independently comprises a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl groups, or substituted or unsubstituted C1-C8 hydroxyalkyl groups; Formula (CII); In formula (CII), R 35 This includes substituted or unsubstituted C2-C6 methylene groups.
16. The separator membrane according to claim 15, wherein, R 35 Each independently includes substituted or unsubstituted C2-C4 methylene groups.
17. The separator membrane according to claim 1, wherein, The liquid-retaining polymer includes an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is formed into a sheet-like structure; the sheet-like structure is in (T m4 The elastic modulus G' - energy dissipation modulus G” curve was obtained by dynamic frequency scanning test at +20℃. The slope of the elastic modulus G' - energy dissipation modulus G” curve is K3, 0.8≤K3<∞, T m4 °C represents the melting temperature of the aldehyde-ketone polymer.
18. The separator membrane according to claim 17, wherein, 0.8≤K3≤100。 19. The separator membrane according to claim 18, wherein, 0.8≤K3≤10。 20. The separator according to claim 17, wherein, The aldehyde-ketone polymer comprises structural units represented by formula (DI) and / or formula (DII). Formula (DI); In formula (DI), R 41 Including single-bonded, substituted, or unsubstituted C1-C6 methylene groups; R 42 Includes hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups; Formula (DII); In formula (DII), R 43 To R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from integers from 0 to 5, and at least one of r and s is selected from a positive integer.
21. The separator according to claim 1, wherein, The molecular weight of the liquid-retaining polymer is 1.2 × 10⁻⁶. 5 g / mol to 1×10 6 g / mol.
22. The separator according to claim 1, wherein, The insulating body includes a substrate, and the polymer layer is disposed on at least one surface of the substrate.
23. The separator according to claim 1, wherein, The insulating body includes a substrate and a heat-resistant coating. The heat-resistant coating is disposed on at least one surface of the substrate, and the polymer layer is disposed on the surface of the heat-resistant coating opposite to the substrate.
24. The separator according to claim 1, wherein, The polymer layer has a coating basis weight of 0.5 mg / 1540.25 mm. 2 Up to 5mg / 1540.25mm 2 .
25. A battery cell comprising a separator as described in any one of claims 1 to 24.
26. A battery comprising a battery cell according to claim 25.
27. An electrical device comprising the battery according to claim 26.
Citation Information
Patent Citations
Preparation method of high-adhesion coating diaphragm and prepared coating diaphragm
CN110690390A
Polymer coating diaphragm with improved structure and preparation method thereof
CN110993859A